2016
DOI: 10.3130/jaabe.15.455
|View full text |Cite
|
Sign up to set email alerts
|

New City Block Design Approaches Incorporating Environmental Assessment for Downtown Districts in Cities with Severe Winter Climates

Abstract: Urban design approaches in many Japanese cities are based on principles that are similar throughout the country without considering the variety in regional climates. Especially in cities with severe winter weather, providing desirable environments for public spaces under conditions of snow and strong winds is an important issue in urban design. This paper proposes new approaches to urban design with environmental assessments using snow and wind simulations to enable the development of original urban design con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Limited studies have been performed on the environmental influence of snow and wind in simulation tests using wind tunnels for urban design. Setoguchi and Watanabe et al considered the urban-design process, including snow and wind environmental assessments for winter cities [8][9][10][11][12][13][14][15]. These studies discussed models that were theoretically planned for developing desirable urban designs.…”
Section: Urban-design Process With Snow and Wind Simulations: A Studymentioning
confidence: 99%
“…Limited studies have been performed on the environmental influence of snow and wind in simulation tests using wind tunnels for urban design. Setoguchi and Watanabe et al considered the urban-design process, including snow and wind environmental assessments for winter cities [8][9][10][11][12][13][14][15]. These studies discussed models that were theoretically planned for developing desirable urban designs.…”
Section: Urban-design Process With Snow and Wind Simulations: A Studymentioning
confidence: 99%
“…Setoguchi et al [32] also proposed a method for estimating the amount of energy required for snow removal using their simulations. Setoguchi et al [28,29] discussed about the low-rise building design and Setoguchi et al [27,[30][31][32] and Watanabe et al [33] discussed about the medium-density buildings with 500-800% Floor Area Ratio (FAR). The 500-800% FAR is equal to the current FAR in downtown Sapporo.…”
Section: Building Design Urban Designmentioning
confidence: 99%
“…Anno [22] Smedley et al [23] Yukawa et al [24] Mitsuhashi [25] Yukawa et al [26] Setoguchi et al [27][28][29][30][31][32] Watanabe et al [33] Kim et al [15], Meng et al [19], Bosselmann et al [20] and Arens et al [21] produced useful studies of downtown San Francisco, California, United States, and they demonstrated the environmental impact of high-and mid-rise buildings using wind simulations conducted solely using a wind tunnel which compared San Francisco's wind conditions in 1985 and 2013 using a wind tunnel [15,[19][20][21]. Kim et al [15] suggested that the planning guidelines enacted since 1985 were effective in improving the wind comfort in public spaces.…”
Section: Building Design Urban Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Baruch (1998) discussed the relationship among building, design, and climate, introducing design principles in different climate regions, broadly including cold regions. Using wind and snow tunnel simulation and evaluation, Setoguchi et al (2004Setoguchi et al ( , 2007Setoguchi et al ( , 2008Setoguchi et al ( , 2009) and Watanabe et al (2016) discussed design procedures for winter cities, especially those suffering heavy snow. They discussed urban structures and building forms which are suitable for outdoor activities in cold season.…”
Section: Introductionmentioning
confidence: 99%